Emerging trends in didactic perspectives in virtual higher education: a bibliometric analysis (2015–2025) - Ortiz-Ordoñez, Kris Evelin; Burbano-Gonzalez, Diana Carolina; Suarez-Muñoz, Jorge Andrés (Frontiers in Education, 2026)
This study adopts a descriptive design to explore emerging didactic perspectives in virtual higher education, focusing on predominant thematic areas in the field. A bibliometric analysis was conducted on a purposive sample of 63 articles published between 2015 and 2025, selected from an initial pool of 2,848 publications indexed in Scopus, Web of Science, and Google Scholar. The study analyzed the frequency and temporal distribution of themes by categorizing titles, abstracts, and keywords. Results showed that humanistic education and digital pedagogy were the most frequently addressed topics, representing over 36% of the publications. Research output increased significantly from 2020, peaking in 2021 with nearly 24% of the total publications. The average annual number of publications was 5.73, with a standard deviation of 5.26, indicating variability over time. Emerging topics such as connectivism, cyberculture, and ethical considerations in virtual education were less represented but are gaining interest. The analysis highlights a growing emphasis on integrating affective, ethical, and relational dimensions into virtual pedagogical practices alongside technological innovation. These findings underscore the evolving nature of research in digital education and provide critical insights for future studies aimed at enhancing inclusivity, engagement, and meaningful learning experiences in virtual higher education environments.